Risk Factors in Pemphigus - Demirci, Gulsen Tukenmez; Mansur, Ayse Tulin; Aydingoz, Ikbal Esen (DERI ZUHREVI HASTALIKLAR DERNEGI, 2011)
Background and Design: There have been reports suggesting the involvement of environmental factors in the disease process of pemphigus. In this study, we aimed to find out the risk factors which could play role in the etiopathogenesis in our pemphigus patients. Material and method: A total of 42 patients (15 male and 27 female) who were diagnosed as pemphigus with histopathological and direct immunoflurosence examinations in our clinic between the years 1998-2004, were interviewed for assessment of regarding with the subjects of the demographic properties, occupational groups, educational level, the number of pregnancies, stressfull life events, diet habits, smoking and alcohol consumption before the onset of the disease and the results were compared to 42 age and gender-matched controls with similar socioeconomic circumstances. Results: Working in agriculture and livestock, multi-parity, absence of smoking and stressfull life events were found to be statistically significant in pemphigus patients than in controls. Conclusion: Working in agriculture and livestock, multi-parity, absence of smoking and stressfull life events were assumed to play role in the etiopathogenesis and course of pemphigus. (Turkderm 2011

45:140-5)
Keywords: Pemphigus; risk factors